USP8 inhibitor RA-9 reduces ACTH release and cell growth in tumor corticotrophs. Issue 8 (28th June 2021) - Treppiedi, Donatella; Di Muro, Genesio; Marra, Giusy; Barbieri, Anna Maria; Mangili, Federica; Catalano, Rosa; Serban, Andreea; Ferrante, Emanuele; Locatelli, Marco; Lania, Andrea G; Arosio, Maura; Spada, Anna; et al.
Abstract : Cushing's disease (CD) is a rare endocrine disorder caused by an adrenocorticotropic hormone (ACTH)-secreting pituitary tumor. Pasireotide is the only pituitary-targeted drug approved for adult patients. Nevertheless, many side effects are encountered and curative therapy is still challenging. Ubiquitin-specific peptidase 8 (USP8) plays a crucial role in the modulation of corticotroph cells growth and ACTH secretion. Here, we explored the anticancer potential of the USP8 inhibitor RA-9 in USP8-WT human tumor corticotroph cells and murine AtT-20 cells. Our results showed that RA-9 causes cell proliferation decrease (−24.3 ± 5.2%, P < 0.01) and cell apoptosis increase (207.4 ± 75.3%, P < 0.05) in AtT-20 cells, as observed with pasireotide. Moreover, RA-9 reduced ACTH secretion in AtT-20 cells (−34.1 ± 19.5%, P < 0.01), as well as in AtT-20 cells transfected with USP8 mutants, and in one out of two primary cultures in vitro responsive to pasireotide (−40.3 ± 6%). An RA-9 mediated decrease of pERK1/2 levels was observed in AtT-20 cells (−52.3 ± 13.4%, P < 0.001), comparable to pasireotide, and in primary cultures, regardless of their in vitro responsiveness to pasireotide. Upregulation of p27 was detected upon RA-9 treatment only, both in AtT-20 cells (167.1 ± 36.7%, P < 0.05) and in one primary culture tested (168.4%), whilst pCREB level was similarly halved in AtT-20 cells by both RA-9 and pasireotide. Altogether, our data demonstrate that RA-9 is efficient in exerting cytotoxic effects and inhibitory actions on cell proliferation and hormone secretion by modulating the expression of pERK1/2, pCREB and p27. Inhibition of USP8 might represent a novel strategy to target both USP8-WT and USP8-mutated tumors in CD patients.